(untitled) - Giyasov, Z.A.; Nazarova, M.M.; Bakhriev, I.I.; Khakimov, S.A.; Vafoyev, Z.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
A comprehensive analysis of medical care defects (MCD) on the materials of the CFME. Material and methods: The object of the study was the materials of the CFME conducted in the Tashkent Regional Bureau of Forensic Medical Examination in 2016-2017. In total, during this period, 51 (38) examinations were conducted about the inadequate provision of medical care to children and adolescents, which accounted for 31.3% of the total number of CFME. The analysis of the obtained results was carried out using comparative, logical and statistical research methods. Results: In total, 52 MCD were verified, since in 11 cases two or more defects were identified. When analyzing the age structure of the patients, it was found that the majority were children under the age of 1 year (55.3%) and 1-3 years (21.1%). 39 (76.5%) defects had a significant impact on the outcome. Moreover, 34 of them, aggravating the condition of children, contributed to the onset of death. More than half of MCD admitted to inpatient medical institutions. About 80% of MCD occur for subjective reasons - due to lack of qualifications or inattention to the patient and have a significant impact on the outcome.